(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Staphylococcus aureus produces epidermolytic toxins that disrupt epidermal cell connections, resulting in staphylococcal scalded skin syndrome (SSSS). Blisters, erythematous cellulitis, and superficial skin peeling characterize this condition. Objective: To provide an overview of the clinical foundation, etiopathogenesis, complications, current treatment options, and potential future advancements in managing SSSS. Methods: This review synthesizes available data on the pathogenesis, clinical manifestations, differential diagnoses, and therapeutic interventions for SSSS. Results: It is classified as a toxin-mediated infection, primarily affecting adults and pediatric patients. Key therapeutic interventions include: • Wound care to protect damaged skin. • Antibiotic therapy with antistaphylococcal medications. • Supportive care with analgesia. Differential diagnoses such as toxic epidermal necrolysis, adverse drug reactions, and Stevens-Johnson syndrome require multidisciplinary evaluation by dermatologists, infectious disease specialists, and surgeons. Conclusion: Effective management of SSSS involves a multidisciplinary approach to reduce mortality. Future developments may enhance understanding and treatment outcomes for this toxin-mediated disease.